2021
DOI: 10.7759/cureus.17527
|View full text |Cite
|
Sign up to set email alerts
|

Uropathogens Antimicrobial Sensitivity and Resistance Pattern From Outpatients in Balochistan, Pakistan

Abstract: To determine the pattern of microbes responsible for urinary tract infections and their susceptibility to different antibiotics. MethodThis is a cross-sectional study conducted at Quetta, Pakistan. The urine samples of 400 patients were collected and sent for culture and sensitivity analysis. The results were recorded on an excel datasheet. Descriptive statistics were used to describe the data. ResultsOut of 400 urine samples, 266 samples were culture positive for microorganisms. The most common organism on an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…In a recent study [15] found that 82.5% of Proteus isolates were MDR. The rate of resistance of P. mirabilis toward ampicillin was (88.3%), piperacillin (72.7%), clindamycin (66.7%), amoxicillin/clavulanic acid (66.2%), and trimethoprim/sulfamethoxazole (50%) is almost exactly in line with the findings reported in [16]. According to [17], [18], gentamycin has a certain effect and P. mirabilis had a greater rate of gentamicin resistance (10.3%).…”
Section: Resultssupporting
confidence: 83%
“…In a recent study [15] found that 82.5% of Proteus isolates were MDR. The rate of resistance of P. mirabilis toward ampicillin was (88.3%), piperacillin (72.7%), clindamycin (66.7%), amoxicillin/clavulanic acid (66.2%), and trimethoprim/sulfamethoxazole (50%) is almost exactly in line with the findings reported in [16]. According to [17], [18], gentamycin has a certain effect and P. mirabilis had a greater rate of gentamicin resistance (10.3%).…”
Section: Resultssupporting
confidence: 83%
“…UTI was most commonly present among females (59.8%) in our study. Similar results have been reported in studies from Iraq (62.7%),[ 18 ] Pakistan (68.0%),[ 23 ] Saudi Arabia (73%),[ 21 ] India (76.6%),[ 20 ] Ethiopia (81.2%),[ 19 ] and South Africa (67.6%). [ 24 ] The increased prevalence of UTI among females might be due to the anatomical differences in urogenital organs between the two sexes.…”
Section: Discussionsupporting
confidence: 88%
“…Among the commonly prescribed broad-spectrum antibiotics, higher resistance was observed against cefotaxime (76.5%), levofloxacin (71.3%), amoxicillin/clavulanate (70.3%), ceftriaxone (64.3%), cefepime (53.4%), and ceftazidime (49.4%). [ 23 ] A study in Iran reported less resistance to E. coli with commonly used antibiotics. [ 26 ] They reported that E. coli was resistant against cefixime (68.2%), ceftriaxone (37%), cotrimoxazole (33.6%), and ciprofloxacin (31.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to earlier studies, the majority of the 137 participants in our research were females [9,10]. This is not unusual and is likely attributed to the anatomy of the female genitourinary system, particularly the shorter urethra and the close proximity of the urethral opening to the anus in females.…”
Section: Discussionsupporting
confidence: 86%